Differentials in literacy in Begusarai district, Bihar: An impediment to sustainable development - Murli Manohar,; Shweta Srivastava,; Gayatri Rai, (National Geographical Journal of India, 2024)
Literacy provides us the ingress to understand a written piece of information and unlatch the door for further education. This acts as a substratum to build upon more advanced skills. The census of India regards a person as literate if he is of 7 years and above and can read and write in any language with understanding. However, significant disparities in literacy levels persist across genders, regions, and social classes, posing challenges to sustainable development. This study focuses on the Begusarai district in Bihar, comprising 18 administrative blocks, to map its literacy landscape. This paper aims to map out the literacy landscape of the Begusarai district and analyze the spatio-temporal aspects of the literacy gap as well as literacy differentials based on gender (male-female) at the block level. The study further attempts to find out the urban-rural differentials in the district and tries to project the level of literacy in the future. The paper also tries to relate the importance of bridging the gap in literacy with sustainable development. The study is based on the data from the District Census Handbook of Begusarai and the census of India for the years 2001 and 2011. Different statistical techniques have been used to calculate the literacy differentials and the future projections of literacy levels in the district. Tabulation and graphical representations have been done with the help of MS Excel software. The ArcGIS10.8 software has been used for cartographical representations. The study reveals that the district is way more literate in 2011 (63.87%) than in 2001 (48%) though there is still a considerable variation in literacy at the inter-block level. The district has bridged the urban-rural gap in literacy (20.64%) at a greater pace than the gender gap (7.13%) in literacy between 2001 and 2011. Notably, a strong inverse correlation (-0.73) exists between total literacy rates and gender differentials, highlighting the district's challenges in achieving gender parity in literacy. The study underscores that disparities in literacy and emphasizes that sustainable development goals can achieved with better access to education and literacy. Efforts to bridge these gaps are crucial for fostering inclusive growth and advancing sustainable development in Begusarai district and beyond.